Management Statement on the Temporary Suspension of Implementing the Policy for Country Contributions for Capacity Building. (Policy Papers; Policy Paper ;, 2009)
This statement provides an update on the implementation of the strengthened country contributions policy for capacity building (the "Policy") and informs the Executive Board of management's intention to suspend temporarily implementation of the Policy. As noted in the Statement of the General Counsel of July 23, 2008, management has the authority to establish and to implement changes to the Policy, in consultation with the Executive Board.